2023
DOI: 10.3390/nu15163627
|View full text |Cite
|
Sign up to set email alerts
|

Aspartame Safety as a Food Sweetener and Related Health Hazards

Shurooq Asaad Abdulameer Shaher,
Dan Florin Mihailescu,
Bogdan Amuzescu

Abstract: Aspartame is the methyl-ester of the aspartate-phenylalanine dipeptide. Over time, it has become a very popular artificial sweetener. However, since its approval by the main food safety agencies, several concerns have been raised related to neuropsychiatric effects and neurotoxicity due to its ability to activate glutamate receptors, as well as carcinogenic risks due to the increased production of reactive oxygen species. Within this review, we critically evaluate reports concerning the safety of aspartame. So… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 121 publications
(281 reference statements)
0
4
0
Order By: Relevance
“…Currently, sugar‐free beverages have been increasingly consumed mainly to reduce calorie intake and prevent obesity and T2DM. While concerns about artificial sweeteners regarding their potential harmful effects on health have been increasingly raised [ 8 , 10 ], SV as a natural sweetener is recognised as a safe sweetener with high sweetness and minimal calories. In this study, we found that SV significantly improved glucose uptake of PA‐treated skeletal muscle cells via the PDK4/AMPK/TBC1D1 pathway, further supporting its use in sugar‐free beverages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, sugar‐free beverages have been increasingly consumed mainly to reduce calorie intake and prevent obesity and T2DM. While concerns about artificial sweeteners regarding their potential harmful effects on health have been increasingly raised [ 8 , 10 ], SV as a natural sweetener is recognised as a safe sweetener with high sweetness and minimal calories. In this study, we found that SV significantly improved glucose uptake of PA‐treated skeletal muscle cells via the PDK4/AMPK/TBC1D1 pathway, further supporting its use in sugar‐free beverages.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence suggesting that artificial sweeteners may increase the risks of cancers, cardiovascular diseases and glucose intolerance [ 8 , 9 , 10 , 11 ]. In contrast, stevioside (SV), as a natural sweetener with no safety concerns reported so far [ 12 ], is 250–300 times sweeter than sucrose but has minimal calories [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A related problem is food sensitivity, in which certain individuals develop various adverse effects, both acute and chronic, including neurobehavioral, gastrointestinal, metabolic, or teratogenic consequences, upon exposure to certain substances, such as gluten, food additives, Fermentable Oligo-, Di-and Mono-saccharides And Polyols (FODMAPs), and non-nutritive sweeteners [7][8][9][10][11][12][13]. There are several examples of these phenomena relevant to the treatment of patients with EDs, including comorbid migraine headaches, irritable bowel syndrome, attention deficit hyperactivity disorder (ADHD), major depressive disorder, and anxiety disorders [12,[14][15][16][17][18][19][20][21][22][23][24][25], in which a nutritional psychiatry perspective can be highly influential [26][27][28].…”
Section: Commentmentioning
confidence: 99%
“…Overall, there seems to be a certain association between aspartame and cancer, but the speci c mechanisms of its impact still require further exploration (Shaher et al, 2023).…”
Section: Introductionmentioning
confidence: 99%